Competition and innovation : in the U.S. fixed-wing military aircraft industry - Birkler, J. L., 1944- (MR (Rand Corporation), 2003)
Responds to Senate's concerns that further consolidation in the military-aircraft industry from its current three prime contractors would pose risks to innovation and cost through limited or no competition in contracting for military aircraft and related weapon systems for the Defense Department. Describes that industry, evaluates what is required to maintain the industry at a high level of innovation, assesses industry?s prospects for innovation and competition, and identifies policy options open to the DoD.